TAHFIDZUL QUR’AN LEARNING MANAGEMENT AT PPI 153 AL-FIRDAUS - Haditsa Qur'ani Nurhakim; Wildan Yahya; A. Mujahid Rasyid (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
Tajiziyyah is a special program held by Al-Firdaus Islamic Islamic Boarding School 153 to prepare the ability to read and memorize the Qur'an, basic knowledge of PAI, and Arabic language skills (qowaid and muhadatsah). This program is held to help students who want to continue the Tsanawiyyah level. Tahfiz Al-Qur'an is a very grand and great task. No one is able to do it except a person who is determined and rounded and wants to be steely. A strong determination owner is someone who is always very enthusiastic and obsessed with realizing what he has intended and moving it with all his might. Maybe every Muslim wants to be able to memorize the Koran. However, desire alone is not enough. This desire should be accompanied by a strong will and will to carry out this sacred duty.Learning management also functions as giving the teacher the authority to carry out his duties as a teacher, who is not only able to provide lessons, but the teacher can also provide input on several teaching policies, and try to implement learning management as well as possible. In this study, researchers used a qualitative approach, while the method used was a case study method. This study tries to explain, investigate and understand the implementation of Islamic boarding schools in shaping the character of santri in Islamic boarding schools, methods or models of character education in Islamic boarding schools, the role of scholars in character education in Islamic boarding schools, and supporting and inhibiting factors faced in implementing character education. Al-Firdaus Cipatat 153 Islamic boarding schools have implemented learning management as follows: Before implementing learning management Islamic boarding schools establish steps by planning learning, implementing learning and evaluating learning. Islamic boarding schools prior to learning always pay attention to the management elements or the formulation of learning management by identifying learning concepts and seeing the objectives to be taught.